Morphological changes in hippocampal cytoarchitecture as a function of spatial treatment in birds. Issue 1 (28th June 2016) - Roth, Timothy C.; Stocker, Kurtis; Mauck, Robert
ABSTRACT: Maintaining cognitive processes comes with neurological costs. Thus, enhanced cognition and its underlying neural mechanisms should change in response to environmental pressures. Indeed, recent evidence suggests that variation in spatially based cognitive abilities is reflected in the morphology of the hippocampus (Hp), the region of the brain involved in spatial memory. Moreover, recent work on this region establishes a dynamic link between brain plasticity and cognitive experiences both across populations and within individuals. However, the mechanisms involved in neurological changes as a result of differential space use and the reversibility of such effects are unknown. Using a house sparrow ( Passer domesticus ) model, we experimentally manipulated the space available to birds, testing the hypothesis that reductions in dendritic branching is associated with reduced Hp volume and that such reductions in volume are reversible. We found that reduced spatial availability associated with captivity had a profound and significant reduction in sparrow hippocampal volumes, which was highly correlated with the total length of dendrites in the region. This result suggests that changes to the dendritic structure of neurons may, in part, explain volumetric reductions in region size associated with captivity. In addition, small changes in available space even within captivity produced significant changes in the spine structure on Hp dendrites. These reductions were reversible following increased spatial opportunities. Overall, these results are consistent with the hypothesis that reductions to the Hp in captivity, often assumed to reflect a deleterious process, may be adaptive and a consequence of the trade‐off between cognitive and energetic demands. © 2016 Wiley Periodicals, Inc. Develop Neurobiol 77: 93–101, 2017